A longitudinal study on quality of life along the spectrum of Alzheimer's disease. (20th December 2022) - Mank, Arenda; Rijnhart, Judith J.M.; van Maurik, Ingrid S.; Jönsson, Linus; Handels, Ron; Bakker, Els D.; Teunissen, Charlotte E.; van Berckel, Bart NM; van Harten, Argonde C.; Berkhof, Johannes; van der Flier, Wiesje M.
Abstract: Background: Quality of life (QoL) is an important outcome from the perspective of patients and their caregivers, in both dementia and pre‐dementia stages. 1 Yet, little is known about the long‐term changes in QoL over time. 2 We aimed to compare the trajectories of the QoL between amyloid‐positive and amyloid‐negative patients along the Alzheimer's disease (AD) continuum of cognitively normal to dementia. Method: In this longitudinal study, we included n = 447 (age 61.6±6.6, n(40%)F, Mini Mental State Examination (MMSE) 29(27‐29), 23% amyloid‐positive) patients with Subjective Cognitive Decline (SCD), n = 276 (age 64.6±7.0, n(33%F), MMSE 27(25‐28), 52% amyloid‐positive) patients with Mild Cognitive Impairment (MCI) and n = 417 (age 64.4±7.0, n(51%F), MMSE 23 (19‐25), all amyloid‐positive) with AD dementia from the Amsterdam Dementia Cohort. We used linear mixed‐effect models (LMM) to compare QoL trajectories of the European Quality of Life‐5 Dimensions (EQ‐5D‐3L and EQ‐5D‐5L) and Visual Analogue Scale (VAS) between 1) amyloid‐positive and amyloid‐negative SCD or MCI patients and 2) amyloid‐positive SCD, MCI, and dementia patients. The models were adjusted for age, sex, Charlson Comorbidity Index (CCI), education and EQ‐5D scale (3 or 5 level). Result: In SCD, amyloid‐positive participants had a higher VAS at baseline, but showed a steeper decline over time in EQ‐5D and VAS than amyloid‐negative participants (figure 1). Also in MCI, amyloid‐positive patients had higher QoL at baseline, but subsequently showed a steeper decline in QoL over time compared to amyloid‐negative patients. When we compared amyloid‐positive patients along the Alzheimer continuum, we found no difference between SCD, MCI or dementia in baseline QoL, but QoL decreased at a faster rate in the dementia stage compared with the pre‐dementia stages of SCD and MCI (figure 2). When we additionally adjusted for covariates in model 2, the effects remained. Conclusion: QoL decreased at a faster rate over time in amyloid‐positive SCD or MCI patients than amyloid‐negative patients. QoL decreases over time along the entire continuum of AD of SCD, MCI and dementia, with the strongest decrease in dementia patients.